Audio Streaming with Silence Detection Using 802.15.4 Radios. (10th December 2012) - Rohankar, A. W.; Pathak, Shantanu; Naskar, Mrinal K.; Mukherjee, Amitava
Abstract : Short-range radios with low data rate are gaining popularity due to their abundant commercial availability. It is imperative that high-speed multimedia would be an attractive application field with these radios. Audio over 802.15.4 compliant radios is a challenging task to achieve. This paper describes a real-time implementation of audio communication using 802.15.4 radios. Silence detection and soft ADPCM are the main features of our work. Our results show that silence detection improves bandwidth optimization and audio communication performance over low bit-rate radios.